PERTUMBUHAN SETEK LADA DARI POHON INDUK YANG DIPUPUK NPKMg DOSIS BERBEDA - Sitti Inderiati; Asmawati Asmawati; Risnawati Risnawati (Jurusan Budidaya Tanaman Perkebunan, Politeknik Pertanian Negeri Pangkajene Kepulauan, 2019)
Pepper plant is propagated through stem cutting to generate a healthy seedling that can further grow vigorously on a cultivation field. A high-quality cutting material produce by healthy mother plant and has sufficient nutrients. To determine a superior pepper mother plant as a source of seedlings, an experiment was carried out using cutting of vine pepper from the fertilized mother plants with NPKMg fertilizers in different dosages. Seedlings of vine cuttings as experimental units were placed in a randomly block design with four treatments as follows: cuttings from fertilized mother plants with 200 g/plant/year of granular NPKMg (H1); cuttings from fertilized mother plants with 50% of the full dosage of liquid NPKMg (H2); cuttings from fertilized mother plants with 75 of the full dosage of liquid NPKMg (H3); cuttings from a fertilized mother plant with full dosage (1600 g NPKMg/plant/year) of liquid NPKMg (H4). Experiment results indicated that pepper seedlings from a fertilized mother plant with full dosage had faster growth of the plants height, greater number of internodes and leaves than other treatments, as well as had bigger stem diameters as compare to seedlings from the fertilized mother plant in lower dosages.